2022
DOI: 10.31083/j.rcm2305176
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation in the Setting of Acute Pneumonia: Not a Secondary Arrhythmia

Abstract: Atrial fibrillation (AF) is the most common arrhythmia in the setting of critically ill patients. Pneumonia, and in particular community-acquired pneumonia, is one of the most common causes of illness and hospital admission worldwide. This article aims to review the association between AF and acute diseases, with specific attention to pneumonia, from the pathophysiology to its clinical significance. Even though the relationship between pneumonia and AF has been known for years, it was once considered a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…Atrial fibrillation (AF) is the most common arrhythmia seen in clinical practice. In some cases, even in the absence of prior history of AF, AF may occur during an acute illness 1 , 2 or may occur in a surgical setting, being more frequently documented after cardio-thoracic surgery (incidence around 30%), 3 but also in noncardiac surgical procedures. 4 In a recent study 5 the rate of postoperative AF (POAF) in the cardiac surgery setting was reported to approximate 20%, whilst in noncardiac surgery it was around 1%.…”
Section: Introductionmentioning
confidence: 99%
“…Atrial fibrillation (AF) is the most common arrhythmia seen in clinical practice. In some cases, even in the absence of prior history of AF, AF may occur during an acute illness 1 , 2 or may occur in a surgical setting, being more frequently documented after cardio-thoracic surgery (incidence around 30%), 3 but also in noncardiac surgical procedures. 4 In a recent study 5 the rate of postoperative AF (POAF) in the cardiac surgery setting was reported to approximate 20%, whilst in noncardiac surgery it was around 1%.…”
Section: Introductionmentioning
confidence: 99%
“…22,46 The interesting study by Zuin et al 30 was conducted before the COVID-19 pandemic that had a major impact on admission to hospitals for AF and AF management. 47 On the one hand, AF incidence increases in the setting of acute illnesses, 48,49 such as COVID-19, 50,51 and its pathogenesis involves a complex interplay between inflammation, prothrombotic state, hemodynamic changes, and sympathetic-vagal imbalances. On the other hand, electrophysiology procedures, as well as admissions and procedures for acute diseases, declined during the subsequent waves of COVID-19 in Italy [52][53][54] and in other European countries, 55 thus potentially accounting for a worsening of patient outcomes.…”
mentioning
confidence: 99%